Construction of Ti3C2 supported hybrid Co3O4/NCNTs composite as an efficient oxygen reduction electrocatalyst. (November 2020) - Liu, Jing; Mi, Liwei; Xing, Yanan; Wang, Tianfu; Wang, Fu
Abstract: Developing high performance non-Pt oxygen reduction reaction (ORR) electrocatalysts is vital for the practical applications of fuel cell but it still remains a grand challenge. Herein, an in-situ pyrolysis strategy was explored to prepare hybrid Co3 O4 /N-doped carbon nanotubes catalyst supported on the surface of Ti3 C2 (Co3 O4 /NCNTs/Ti3 C2 ). Owing to the synergistic effects of constituent components, as-prepared Co3 O4 /NCNTs/Ti3 C2 exhibited superior ORR activity (diffusion limited current 5.41 mA cm −2 and half-wave potential 0.79 V) to the commercial Pt/C (diffusion limited current 5.14 mA cm −2 and half-wave potential 0.78 V). Meanwhile, the Co3 O4 /NCNTs/Ti3 C2 catalyst demonstrated moderately good stability. Compared with the loss of current (∼54%) of commercial Pt/C, 48% current decrease was observed for Co3 O4 /NCNTs/Ti3 C2 after the chronoamperometric measurement for 6 × 10 3 s. In view of the enhanced activity and stability, Co3 O4 /NCNTs/Ti3 C2 holds high potential as a practical ORR electrocatalyst. Highlights: A novel type of composite Co3 O4 /NCNTs/Ti3 C2 was prepared. An in-situ pyrolysis strategy was employed. Higher ORR activity of Co3 O4 /NCNTs/Ti3 C2 than that of commercial Pt/C. The moderately high stability of Co3 O4 /NCNTs/Ti3 C2 in 0.1 M KOH.